Attitude of Iranian state university students to general lexical items created by APLL / Ehsan Barzegar - Barzegar, Ehsan (2015)
This study focuses on the attitudes of Iranian state university students towards the neologisms suggested by Academy of Persian Language and Literature (APLL). A questionnaire-based survey was administered to 500 students in Tehran. This was followed by interviews with 21 students as well as 5 APLL experts to supplement and probe the data. Being familiar with/interested in APLL and its activities by approximately 40%, participants seem to have low attitude towards APLL and its success in word-creation by 41%. This figure decreases to 33.3% as to the interviews. Concerning the involvement of linguists and men of letters in creating neologisms, 100% of APLL experts and over 63% of students queried/interviewed believed both groups should cooperate with each other when deciding on new words. Regarding the use of APLL words by reporters/newsreaders, the public, participants’ family and professors, only 38% of interviewees believed these individuals use the words whereas this percentage is 47.7% and 63.3% by respondents of questionnaires and APLL experts, respectively. Participants adopted a rather high positive attitude towards using living elements in Persian (72.8%), utilizing both classic and contemporary books (over 70%) through referring to works by poets/writers/translators to create new words. These figures decreased to 62.3% and 60.7% regarding the use of different accents/dialects, and the experiences/knowledge of other countries, respectively, for creating neologisms. Respondents reflected a rather high attitude towards the importance of certain word features for creating neologisms in Persian by approximately 70%. Their choices in order of preference included semantic transparency, eusemy, euphony, brevity and productivity. This was true with APLL experts except for productivity as being their second choice. Respondents expressed a rather moderate attitude towards the importance of familiarity with foreign language(s) for accepting APLL words (62.8%), necessity of allocating some part of Persian Literature at universities to word-creation (approximately 57%) and creating a database for APLL activities in the Internet (about 64%). There was a rather high positive attitude towards the extent to which reporters/newsreaders use APLL words (74.4% and 86.1%, respectively). Nonetheless, the public and participants’ families seemed to be using neologisms to a small extent (about 30%). However, this figure increases to 53.6% by university professors. Participants adopted high positive attitudes towards TV, radio and newspapers for promoting neologisms. Other media such as cinema, satellites, SMS, theatre and the Internet are said to be moderately or (very) little important. Concerning certain demographic variables, there was no correlation between participants’ attitude towards the APLL (words) and their gender, age, place of residence, fields of study and level of education. However, participants with more educated parents were a slightly less favourable about the APLL products. Meanwhile, there was no correlation between participants’ knowledge of foreign language(s) as well as their use of accents/dialects other than Persian and their accepting the APLL words. Except for productivity, there was no correlation between respondents’ attitudes towards other word features and the acceptance of APLL words. This was true with participants’ activities (such as reading newspaper/magazines) and their accepting the neologisms except for literary books/materials.